2019
DOI: 10.3847/2041-8213/ab58d1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Outskirts of Globular Clusters: The Peculiar Kinematics of NGC 3201

Abstract: The outskirts of globular clusters (GCs) simultaneously retain crucial information about their formation mechanism and the properties of their host galaxy. Thanks to the advent of precision astrometry both their morphological and kinematic properties are now accessible. Here we present the first dynamical study of the outskirts of the retrograde GC NGC3201 until twice its Jacobi radius (< 100 pc), using specifically-selected high-quality astrometric data from Gaia DR2. We report the discovery of a stellar over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 61 publications
(70 reference statements)
4
25
0
Order By: Relevance
“…Since the pioneering work of Leon et al (2000), an ever-increasing list of globular clusters have been found to possess tidal tails (e.g., Odenkirchen et al 2001;Ibata et al 2019a;Palau & Miralda-Escudé 2019;Bianchini et al 2019;Thomas et al 2020;Sollima 2020). The present work reveals that at least 11 clusters have exceedingly long tidal tails with numerous member stars measured with exquisite astrometric precision in the Gaia DR2 and EDR3 catalogs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Since the pioneering work of Leon et al (2000), an ever-increasing list of globular clusters have been found to possess tidal tails (e.g., Odenkirchen et al 2001;Ibata et al 2019a;Palau & Miralda-Escudé 2019;Bianchini et al 2019;Thomas et al 2020;Sollima 2020). The present work reveals that at least 11 clusters have exceedingly long tidal tails with numerous member stars measured with exquisite astrometric precision in the Gaia DR2 and EDR3 catalogs.…”
Section: Discussionsupporting
confidence: 53%
“…NGC 3201 is also a low-latitude globular cluster that is suffering tidal stripping (Bianchini et al 2019). The STREAMFINDER is able to identify a 12 • -long feature in the immediate vicinity of the cluster, as we show in Figure 12.…”
Section: Ngc 3201 and Gjöllmentioning
confidence: 99%
“…It could be possible that some remnant of the DM halo is still preserved in the peripheries of present-day GCs (e.g. see Heggie & Hut 1996;Baumgardt et al 2009;Lane et al 2010;Conroy et al 2011;Ibata et al 2013;Penarrubia et al 2017;Bianchini et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As we are searching for outlying stars that belong to the cluster, the proper motion for the cluster and extended structure components are assumed to be identical. This is a reasonable assumption since the proper motion should not vary significantly over the area on the sky that we are exploring (e.g., Bovy et al 2016;Bianchini et al 2019). We also fit the dispersion of the MW contaminant and cluster components.…”
Section: The Methodsmentioning
confidence: 99%